2012
DOI: 10.1111/j.1471-4159.2012.07823.x
|View full text |Cite|
|
Sign up to set email alerts
|

Vimentin participates in microglia activation and neurotoxicity in cerebral ischemia

Abstract: J. Neurochem. (2012) 122, 764–774. Abstract Microglia are the ‘immune cells’ of the brain and their activation plays a vital role in the pathogenesis of many neurodegenerative diseases. Activated microglia produce high levels of pro‐inflammatory factors, such as TNFα, causing neurotoxicity. Here we show that vimentin played a key role in controlling microglia activation and neurotoxicity during cerebral ischemia. Deletion of vimentin expression significantly impaired microglia activation in response to LPS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 37 publications
(46 reference statements)
2
45
0
Order By: Relevance
“…Two of the significantly dysregulated proteins, namely vimentin and 2′,3′-cyclic-nucleotide 3′-phosphodiesterase (CNP) were chosen for further validation using Western blotting, as changes of both vimentin and CNP have been previously reported in rodent models of ischemic stroke232425. Vimentin expression was markedly up-regulated in the ipsilateral (Ipsi) region of the brain compared to that of the contralateral part.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the significantly dysregulated proteins, namely vimentin and 2′,3′-cyclic-nucleotide 3′-phosphodiesterase (CNP) were chosen for further validation using Western blotting, as changes of both vimentin and CNP have been previously reported in rodent models of ischemic stroke232425. Vimentin expression was markedly up-regulated in the ipsilateral (Ipsi) region of the brain compared to that of the contralateral part.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Vimentin is a component of the intermediate filament system and a prominent marker of microglia and reactive astrocytes23. Up-regulation of vimentin demonstrates that microglia and reactive astrocytes are activated and/or are proliferating in response to the presence of injured neural tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vimentin can activate microglia and astrocytes to aggravate neurotoxicity and impairment. Deleted vimentin can alleviate microglia activation and neuron damage [45,46]. In this study, a high-level of vimentin increase was observed in the APP/PS1-ShDbn1 mice.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, by treating KPV +/+ mice with WFA following tumor development, we show that the delayed tumor growth and metastasis observed in KPV −/− mice in Figure 1 is not due solely to delayed onset of tumor growth, but rather to attenuated growth kinetics in tumor cells that lack an intact vimentin network. Although vimentin-null mice were first reported to display no obvious phenotype, these data and others suggest that loss of vimentin is protective against a range of challenges including lung cancer, lipopolysaccharides, bleomycin, asbestos, bacterial meningitis, cerebral ischemia, and acute colitis (26, 38, 6264). While this study adds to the body of knowledge on the phenotype of the vimentin-null mouse, the global knockout model presents limitations.…”
Section: Discussionmentioning
confidence: 95%